2021
DOI: 10.12998/wjcc.v9.i21.6145
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary diagnostic dilemma in differentiating Madelung’s disease — the value of superb microvascular imaging technique: A case report

Abstract: BACKGROUND Madelung’s disease, also known as multiple symmetrical lipomatosis, is a rare, underrecognized disorder of fat metabolism that results in unusual accumulation of subcutaneous fat deposits around the neck, shoulders, upper arms, trunk, hips, and upper thighs. Our case demonstrates the importance of differential diagnosis and the value of a superb microvascular imaging technique for suspecting and confirming Madelung’s disease. Timely diagnosis and alcohol abstinence could prevent the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…One study reported that an MD patient with type 2 diabetes was treated conservatively[ 29 ]. The second study reported a superb microvascular imaging technique for suspecting and confirming MD[ 30 ], and the third case study reported that a patient had a concomitant incarcerated femoral hernia and had undergone surgical treatment for complications but did not receive surgery for the masses secondary to MD[ 8 ]. We proposed a staged operation plan to remove the masses in our patient to reduce the risk of postoperative hematomas or seromas and to prevent airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that an MD patient with type 2 diabetes was treated conservatively[ 29 ]. The second study reported a superb microvascular imaging technique for suspecting and confirming MD[ 30 ], and the third case study reported that a patient had a concomitant incarcerated femoral hernia and had undergone surgical treatment for complications but did not receive surgery for the masses secondary to MD[ 8 ]. We proposed a staged operation plan to remove the masses in our patient to reduce the risk of postoperative hematomas or seromas and to prevent airway obstruction.…”
Section: Discussionmentioning
confidence: 99%